Germline genetic host factors as predictive biomarkers in immuno-oncology. (September 2019) - Chat, Vylyny; Ferguson, Robert; Kirchhoff, Tomas
Abstract : In immuno-oncology (IO), the baseline host factors attract significant clinical interest as promising predictive biomarker candidates. Growing evidence from experimental or population-based studies suggests that the host genetic factors contribute to the immunological status of a patient as it plays out at the multiple rate-limiting steps of the cancer immunity cycle. Recent observations suggest that germline genetics may be associated with tumor microenvironment phenotypes, autoimmune toxicities and/or efficacy of immunotherapy regimens and overall cancer survival. Despite these highly intriguing indications, the potential of germline genetic factors as personalized biomarkers of immune-checkpoint inhibition (ICI) remains vastly unexplored. Here, we review the rationale for exploring the germline genetic factors as novel biomarkers predictive of IO outcomes, including ICI efficacy, toxicity and survival, and discuss the comprehensive approaches for the identification of such germline genetic indicators. In addressing the current limitations, we highlight a need for large collaborative consortia in these efforts. We also outline possible avenues for incorporating germline genetic factors into emerging multifactorial tools for a more personalized prediction of ICI outcomes. Highlights: Growing evidence links germline genetic variation and host immunity. Immune-checkpoint inhibition (ICI) therapies may be impacted by germline genetics. Autoimmune genetic risk may be an important indicator of ICI efficacy and toxicity. ICI germline underpinning needs to be explored in newly established immuno-oncology (IO) consortia. Germline factors may serve as novel IO biomarkers and possibly new IO targets.